2022
DOI: 10.1007/s13398-022-01305-6
|View full text |Cite
|
Sign up to set email alerts
|

Closed linear spaces consisting of strongly norm attaining Lipschitz functionals

Abstract: Given a pointed metric space M, we study when there exist n-dimensional linear subspaces of $$\mathrm {Lip}_0(M)$$ Lip 0 ( M ) consisting of strongly norm-attaining Lipschitz functionals, for $$n\in {\mathbb {N}}$$ n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the past few years, this topic has been intensively studied. We send the reader to [1,2,3,4,5,6,7,11,12,14,15,17,18,19] and the references therein.…”
Section: Preliminaries and Notationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few years, this topic has been intensively studied. We send the reader to [1,2,3,4,5,6,7,11,12,14,15,17,18,19] and the references therein.…”
Section: Preliminaries and Notationmentioning
confidence: 99%
“…We consider the subset SNA(M) of Lip 0 (M) of all strongly norm-attaining Lipschitz functions on M. In 2016, Marek Cúth, Michal Doucha, and Przemysław Wojtaszczyk [8] proved that ℓ ∞ (and hence c 0 ) embeds isomorphically in Lip 0 (M) for any infinite metric space M. One year later, this result was improved by Marek Cúth and Michal Johanis and it is known now that ℓ ∞ (and hence c 0 ) embeds isometrically in Lip 0 (M) [9]. Motivated by the papers [1,13,19], we turn our attention to the study of the analogous problems for the subset SNA(M). Drastically different from the classical norm-attaining theory, where Martin Rmoutil [21] proved that the set of all norm-attaining functionals needs not contain 2-dimensional spaces, Antonio Avilés, Gonzalo Martínez Cervantes, Abraham Rueda Zoca, and Pedro Tradacete [1] provided a beautiful and interesting construction, and showed that SNA(M) contains an isomorphic copy of c 0 for every infinite metric space M (answering [19,Question 2]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation